Dé-finir le langage dans The Names de Don DeLillo - Karim Daanoune (Sillages Critiques)
Haunted by terror, Don DeLillo’s 1982 international novel The Names is teleologically drawn towards death. Hiding in the hills and gathered around an unusual pseudo-spiritual belief, a terrorist cult tracks and kills anyone “whose initials matched the first letter of each word in a particular place-name » (168). This lethal equation rests on an implacable and absurd mathematical formula where letters have superseded numbers. In other words, the cult meticulously conjugates language with death by conflating the origin and the end of language in a single performative gesture. This teleological movement or death-drive is at the heart of many of Don DeLillo’s fictions and has been brilliantly summed up by one of his most famous characters, Jack Gladney: “All plots tend to move deathward. This is the nature of plots” (White Noise, 26). The cult’s search for a form of artificial transcendence tends to privilege the end as a totalizing principle of closure. Yet, the novel offers as a counterpoint against the end and at the end the unexpected fiction of Tap, the son of James Axton, the narrator. Liberating by its inner vitality and originality, Tap’s literary work thwarts both terror and death. His short narrative enables an ever-renewed otherness of language, not only in his playful mispelling of words, but also in the prospective character of the meaning attached to them, a meaning that is always to come and that operates in the Derridean supplementary mode. Tap’s writing, notwithstanding its final position in the novel—or perhaps because of that very position—precludes it from ending.